The Role of Family Education in Facing Millenial Era Through Moral Development in Children - Laely Rizki Amalia; Anggi Setiyaningsih; Haani Aulia Sabrina; Joharman Joharman; Siti Fatimah (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2019)
Education is a conscious and planned effort to realize the atmosphere and learning process of students so that they can actively develop their potential to have spiritual, religious, self-control, intelligence, noble character, and skills needed by themselves and the community. Given in this millennial era, technology is increasingly sophisticated and advanced. The threat that may not be realized by the current generation is the moral degradation of the nation. The role of the family in educating children in the millennial era takes a very important role in overcoming this, so children need intensive supervision from parents. The family as a foundation for character and character for children. Education and character formation of children can’t be separated from parenting parents. Where the relationship between parents and children can be established properly, so that automatically an agreement occurs in every decision making. The education bureaucracy must be able to focus on strategic policies and be able to create and be able to bridge between the pure values of the nation and existing developments.